The Effectiveness Of Using Songs And Dialogues To Teach Students’ Pronunciation - Izzah, Ummul; Sukrisno, Alim (English Education Journal, 2017)
This research was conducted to observe fourty eight seven graders of SMP N 17 Pekalongan’s pronunciation ability in pronouncing the simple phrases. The participants were divided equally into two groups for the experimental research. The first group used songs in teaching and learning the pronounciation and another group used dialogues. The data of this study were taken from the recorded voice that we transcribed and the teacher’s notes. Based on the transcription we gave the score based on the score rubrics we made before. The analysis was observed quantitively from the recordings, transcription, scores based on the score rubrics from the pre-test and the post-test, and the teacher’s notes which were taken during and after the lesson. We analyze and describe the result based on the data and used SPSS and t-table to analyze the post-test. The result showed that in general, the group used songs produced better result than the group used dialogues. The participants that used songs tended to attend the pronunciation class more willingly and showed more enthusiasm in conducting the activities. Meanwhile the participants that used dialogues were distracted after hearing the songs sung in the group that used songs. It is suggested that teachers must know how to control the situation and to keep the students from disturbing other classes because sometimes singing songs make the students over enthusiastic.